Manufacturing the future: is the manufacturing sector a driver of R&D, exports and productivity growth? - Alexander Coad; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2017)
Many industrialized countries in Europe and North America have experienced a steady decline in the manufacturing sector over the last few decades. Amid growing concerns that outsourcing and offshoring have destabilized European economies, policymakers have suggested that a large manufacturing sector can: i) boost R&D, ii) encourage exporting, and iii) raise productivity. We examine these claims. Non-parametric plots and regressions show a robust positive association between the manufacturing sector and Business R&D expenditures (BERD), while the relationship between manufacturing and exports or productivity is more elusive. Finally, we explore whether a manufacturing sector target of 20% of value-added will help reach a BERD target of 3% of GDP.
Keywords: O3; O14; O47; 330; Manufacturing sector; R&D; exporting; productivity; industrial policy; industrial renaissance